The need for family counseling to support children with autism (Comprehensive Journal of Science, 2026)
Having a child with autism in the family presents multiple challenges related to their characteristics and needs. This necessitates a significant, demanding, and effective role in developing and enhancing their abilities through comprehensive care and inclusion within the family. It also requires providing the child with the necessary experiences to adapt to their social environment. Furthermore, it highlights the social and humanitarian need for psychological and social counseling services. The importance of family counseling is evident in raising awareness among families of children with autism and fostering a sense of responsibility within the family.This research aimed to uncover the behavioral characteristics of children with autism and to identify family counseling methods for supporting and developing their abilities. The researcher concluded that family counseling is one of the most important approaches to caring for and supporting children with autism. Furthermore, training parents to understand the difficulties their children with autism face contributes to acquiring information, developing skills, and learning how to interact with them.
Keywords: Family counseling - Child with autism - Need - Support